2014
DOI: 10.1002/jso.23578
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic finding determined outcome after chemoradiotherapy in esophageal cancer patients with airway invasion

Abstract: Bronchoscopic finding determined outcome after CRT in esophageal cancer patients with airway invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…There are several studies that investigated the location of airway involvement, which may be associated with unfavorable outcome. Yin et al 18 found that an esophageal tumor that involved the carina was one of the predictors for poor survival. Because of the anatomical complexity of the carina, bronchoscopic intervention could be challenging and it is sometimes difficult to select the appropriate stent for airway restoration.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that investigated the location of airway involvement, which may be associated with unfavorable outcome. Yin et al 18 found that an esophageal tumor that involved the carina was one of the predictors for poor survival. Because of the anatomical complexity of the carina, bronchoscopic intervention could be challenging and it is sometimes difficult to select the appropriate stent for airway restoration.…”
Section: Discussionmentioning
confidence: 99%